Suitability and Carrying Capacity Analysis of Marine Ecotourism at Bahak Beach, Probolinggo Regency, East Java - Primyastanto, Mimit; Puspa Wardani, Mentari; Supriyadi, Supriyadi; Febryane Adhani Mazaya, Amalia; Dwi Nadila, Ema; Koni’Atun Nisa’, Septiana; Ardi Susanto, Farhan; Muhtar Efendi, Bagas (Universitas Islam Lamongan, 2025)
Bahak Beach is one of the destinations that has been developed into a marine tourism area in Probolinggo Regency. Bahak Beach offers various tourist attractions, utilizing the presence of mangrove and beach ecosystems. The objective of this research is to analyze the suitability and carrying capacity of the marine ecotourism area at Bahak Beach, Probolinggo Regency. The research was conducted in October 2024. The data for this research were obtained through primary sources, using structured observations and interviews. This study employs a quantitative descriptive method, with data analysis focused on carrying capacity and the Tourism Suitability Index (IKW). The results of the carrying capacity analysis for the marine ecotourism area at Bahak Beach show a value of 74% (Moderately Suitable) and Carrying Capacity analysis yielded the equation PCC > RCC > ECC with values of 1934 > 1221 > 244. The analysis of the Tourism Suitability Index (IKW) for the tourist attractions at Bahak Beach reached 75% (Highly Suitable). It is recommended to further develop and sustain the marine ecotourism at Bahak Beach by adding attractions for children and enhancing the competencies of ecotourism managers through training.